From theory to practice: a participatory HR-led training programme for employee wellbeing - Shekhar, Anurag; Saurombe, Musawenkosi Donia; Joseph, Renjini Mary (Frontiers in Organizational Psychology, 2025)
IntroductionThis study aimed to design a structured, HR-led training programme to enhance employee well-being in the workplace, addressing the global decline in engagement and mental health.MethodsConducted within a South African organization, the intervention followed a three-phase qualitative design: a pilot training session introducing 25 evidence-based wellbeing constructs, a focus group discussion (FGD) to prioritize constructs based on participant relevance, and thematic analysis to co-develop the final content.ResultsParticipants identified six priority constructs—relationships, physical health (sleep, nutrition, exercise), mental health (mindfulness, gratitude, optimism), Job health (character strengths, job crafting) and meaning in life—which formed the foundation of the ENGAGE training programme. Delivered in a 2-day classroom format, the programme resulted in significant improvements in mental wellbeing, as measured by the WEMWBS, detailed in a separate publication.DiscussionThis research demonstrates that HR professionals, even without clinical expertise, can co-create and deliver impactful wellbeing interventions. The participatory design ensured cultural relevance, high engagement, and strong practical applicability. Unlike fixed, top-down models, the ENGAGE framework reflects employee voice and workplace realities, contributing a locally grounded, evidence-informed approach to the field of workplace wellbeing. It offers both conceptual and practical value for HR practitioners and researchers aiming to enhance wellbeing through structured, scalable interventions.